Central-Approach Surgical Repair of Coarctation of the Aorta with a Back-up Left Ventricular Assist Device for an Infant Presenting with Severe Left Ventricular Dysfunction - Kim, Tae Hoon (Korean J Thorac Cardiovasc Surg, 2015)
A two-month-old infant presented with coarctation of the aorta, severe left ventricular dysfunction, and moderate to severe mitral regurgitation. Through median sternotomy, the aortic arch was repaired under cardiopulmonary bypass and regional cerebral perfusion. The patient was postoperatively supported with a left ventricular assist device for five days. Left ventricular function gradually improved, eventually recovering with the concomitant regression of mitral regurgitation. Prompt surgical repair of coarctation of the aorta is indicated for patients with severe left ventricular dysfunction. A central approach for surgical repair with a back-up left ventricular assist device is a safe and effective treatment strategy for these patients.